Filozofia polityczna a pozytywistyczna teoria prawa - Gizbert-Studnicki, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The purpose of the paper is to explore the question whether the positivistic legal theory may bedeveloped without any assumptions pertaining to political philosophy. The legal theory of H.L. Hartis examined. The author comes to the conclusion that Hart (notwithstanding the declaration thathis theory is purely descriptive) adopts certain tacit evaluative assumptions, and, therefore doesnot maintain absolute neutrality vis-a-vis political values. Hart’s assumption are, however, minimaland therefore uncontroversial. This causes that his theory is not able to propose a satisfactory explanationof the normativity of law. Various understandings of the role of a legal theory in such anexplanation are discussed.
Keywords: filozofia polityczna; teoria prawa; pozytywizm prawniczy; Wielka Brytania